An Overview Of Medicinal Plants Used For Anti-Aging Face Pack Formulation (Journal of Pharmaceutical Negative Results, 2023)
Now a days the pharmaceutical sciences has let to huge and creative evaluation in the field of medicines and cosmetics. Various types of formulation like face packs, creams, lotion etc. are used for multiple purposes like altering appearance, creating a glowing effect and also for anti-ageing effect. In the recent times, many pharmaceutical industries are creating this substance by using both i.e., natural substances and also artificial synthesis substances in higher rate but more inclined towards producing with natural and ayurvedic substances or in simple terms with herbal medication because the demand of herbal cosmetic is growing in an alarming rate. Many natural substance and herbs which are widely available are used in different concentration and for different purposes like sandal wood, turmeric, aloe vera, nutmeg, tulsi, mushroom, papaya. Anti-ageing is now a days one of the biggest effects that every industry is targeting or focusing to achieve. Ageing is now a days one of the biggest issues faced by specially women all over the world and its onset is around when they reach the age over 40. The need for creating substances with anti-ageing effects is because the life style now a days people are maintaining is not good for them which can lead to earlier health issues like denaturation of collagen which helps in maintaining the elasticity property of the skin and the need for going to create with natural substances is because they have got least side effects and almost no toxicological effects. There are various types of pre-formulation consideration and different evaluation parameters for creating this medication or preparation. In this article, the readers will get to know about all the information which could be helpful to them and would create a sense of knowledge inside them.